EFFECT OF DEGUSSA P25 CONTENT ON THE DEPOSITION OF TiO2 COATING ON CERAMIC SUBSTRATE - Musa, M.A.; Juoi, J.M.; Rosli, Z.M.; Johari, N.D.; Moriga, T. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
TiO2 coatings were deposited on unglazed ceramic tiles to study the property of its antimicrobial activity. Here, the effect of TiO2 nanoparticles content (Degussa P25) on the TiO2 coatings’ characteristics was investigated. TiO2 sol containing 25, 50, and 100 g/L Degussa P25 were deposited few times on ceramic tiles via sol-gel dip coating method and heat treated at 500°C. The coatings were analyzed using SEM and the phases were characterized using GAXRD. The results show that Degussa P25 content significantly influences the TiO2 coatings morphology and thickness. Increasing the Degussa P25 content led to a thicker and denser coating with different Degussa P25 content yielded different thickness at specific dipping time. 50 g/L of Degussa P25 was discovered as the maximum amount to be used for achieving good adherence coating on the ceramic tiles. Five dipping of TiO2 sol containing 50 g/L Degussa P25 was found appropriate to generate coating of continuous layer with average thickness of ~29 µm. The Degussa P25 content, however, shows insignificant effect on coating crystallinity.